2013
DOI: 10.1111/nph.12653
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing provides insight into the reproductive biology, nutritional mode and ploidy of the fern pathogenMixia osmundae

Abstract: SummaryMixia osmundae (Basidiomycota, Pucciniomycotina) represents a monotypic class containing an unusual fern pathogen with incompletely understood biology. We sequenced and analyzed the genome of M. osmundae, focusing on genes that may provide some insight into its mode of pathogenicity and reproductive biology.Mixia osmundae has the smallest plant pathogenic basidiomycete genome sequenced to date, at 13.6 Mb, with very few repeats, high gene density, and relatively few significant gene family gains.The gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 70 publications
3
25
0
Order By: Relevance
“…These studies have shown that rust fungi exhibit very large genome sizes [ Melampsora lini = Mli (Nemri et al, 2014) is the largest fungal genome so far] compared to other fungi, containing very large numbers of genes, over 16,000 in most cases, compared to other fungi groups such as Ustilaginomycotina [ U. maydis = 6786 protein coding genes (Schirawski et al, 2010)] or other non-rust Pucciniomycotina such as Mixia osmundae (Toome et al, 2014). Rusts also show a large content in transposable elements (i.e., nearly 50%, in the genomes analyzed so far, Duplessis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that rust fungi exhibit very large genome sizes [ Melampsora lini = Mli (Nemri et al, 2014) is the largest fungal genome so far] compared to other fungi, containing very large numbers of genes, over 16,000 in most cases, compared to other fungi groups such as Ustilaginomycotina [ U. maydis = 6786 protein coding genes (Schirawski et al, 2010)] or other non-rust Pucciniomycotina such as Mixia osmundae (Toome et al, 2014). Rusts also show a large content in transposable elements (i.e., nearly 50%, in the genomes analyzed so far, Duplessis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Lower quality genomes were excluded based on sequencing read coverage, number of scaffolds, and sizes of the longest scaffolds, with the exception of the endophytes, which were all retained. These species include: symbiotic endophytic fungi [ Daldinia eschscholtzii , Rhodotorula graminis (Firrincieli et al 2015), Xylona heveae (Gazis et al 2016)], mycorrhizal fungi [ Cenococcum geophilum , Choiromyces venosus , Cortinarius glaucopus , Gyrodon lividus , Hebeloma cylindrosporum (Kohler et al 2015; Dore et al 2015), Laccaria bicolor (Martin et al 2008), Meliniomyces bicolor (Grelet et al 2009), Oidiodendron maius (Kohler et al 2015), Paxillus involutus (Kohler et al 2015), Pisolithus tinctorius (Kohler et al 2015), Terfezia boudieri , Tuber melanosporum (Martin et al 2010), and Wilcoxina mikolae )] and plant pathogens [ Bipolaris sorokiniana (Ohm et al 2012; Condon et al 2013), Blumeria graminis (Spanu et al 2010), Botryosphaeria dothidea , Botrytis cinerea (Staats and van Kan 2012; Amselem et al 2011), Cercospora zeae-maydis , Colletotrichum graminicola (O’Connell et al 2012), Cronartium quercuum , Didymella exigua , Fomitiporia mediterranea (Floudas et al 2012), Fusarium graminearum (Cuomo et al 2007), Leptosphaeria maculans (Rouxel et al 2011), Magnaporthe oryzae (Dean et al 2005), Mixia osmundae (Toome et al 2014), Passalora fulva (de Wit et al 2012; Ohm et al 2012), Phaeosphaeria nodorum (Hane et al 2007), Sclerotinia sclerotiorum (Amselem et al 2011), Setosphaeria turcica (Ohm et al 2012; Condon et al 2013), Sporisorium reilianum (Schirawski et al 2010), Verticillium alfalfae (Klosterman et al 2011), and Zopfia rhizophila ]. Transcript sequences were downloaded for all species, also from the JGI database.…”
Section: Methodsmentioning
confidence: 99%
“…fusiforme G11 version 1.0 ( Cqf ; unpublished, jgi.doe.gov/Cronartium), Melamspora larici-populina version 1.0 ( Mlp ; Duplessis et al, 2011a,b), Puccinia graminis f.sp. tritici CRL 75-36-700-3 race SCCL ( Pgt ; Duplessis et al, 2011a,b), Mixia osmundae IAM 14324 version 1.0 ( Mos ; Toome et al, 2014), Sporobolomyces roseus version 1.0 ( Sro ; with permission; jgi.doe.gov/fungi), Rhodotorula graminis strain WP1 version 1.1 ( Rgr ; with permission; jgi.doe.gov/fungi), Ustilago maydis strain 521 ( Uma ; Kamper et al, 2006), Malasezzia globosa CBS 7966 ( Mgl ; Xu et al, 2007), Pisolithus tinctorius Marx 270 version 1.0 (Pti; with permission; jgi.doe.gov/fungi), Phanerochaete chrysosporium version 2.0 ( Pch ; Martinez et al, 2004), Heterobasidion irregulare version 2.0 ( Hir ; Olson et al, 2012), Serpula lacrymans S7.3 version 2.0 ( Sla ; Eastwood et al, 2011), Agaricus bisporus var. bisporus H97 version 2.0 ( Abi ; Morin et al, 2012), Laccaria bicolor version 2.0 ( Lbi ; Martin et al, 2008), Amanita muscaria Koide version 1.0 ( Amu ; with permission; jgi.doe.gov/fungi), and (Ascomycota) Saccharomyces cerevisiae S288C ( Sce ; Goffeau et al, 1996), for a total of 200,313 proteins.…”
Section: Methodsmentioning
confidence: 99%